Marmaton Watershed Assessment: Preliminary Report - Nejadhashemi, A. P.; Gali, R.K.; Smith, C.M.; Mankin, K.R.; Wilson, R.M.; Brown, S.P.; Leatherman, J.C. (My University, 2009)
A preliminary assessment of the Marmaton Watershed in southeast Kansas.
EP138_2009-02
Keywords: EP138; Environment and Natural Resources; EP